A two-fold challenge: the experience of women of color in genomics. Issue 1 (December 2016) - Chen, Ling-Ling; Claw, Katrina; Ramachandran, Sohini
Abstract What can be done to encourage and support women of color in STEM fields?Genome Biology spoke with three women of color who have had success in the area of genomics research.